2020
DOI: 10.1111/cid.12913
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructive therapy for the management of peri‐implantitis via submerged guided bone regeneration: A prospective case series

Abstract: Background: The present case series assesses the response to reconstructive therapy for the management of 2/3-wall peri-implantitis bone defects following submergedhealing guided bone regeneration. Material and Methods: Fifteen consecutive patients with 27 implants presenting periimplantitis were included. Guided bone regeneration was applied by means of autogenous bone/deproteinized bovine bone mineral grafting mixture and collagen membrane. Patients were assessed at baseline (T0) and at 6 (T1) and 12 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 35 publications
1
52
0
17
Order By: Relevance
“…Data on patient‐related outcomes following reconstructive surgery of peri‐implantitis are limited (Tomasi et al, 2019). However, in a recent publication, patient's site‐specific comfort during oral hygiene was evaluated, and the authors reported that this improved following surgical therapy (Monje et al, 2020). In the present study, high scores were reported for OHIP‐14, and almost all patients were satisfied with the results of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Data on patient‐related outcomes following reconstructive surgery of peri‐implantitis are limited (Tomasi et al, 2019). However, in a recent publication, patient's site‐specific comfort during oral hygiene was evaluated, and the authors reported that this improved following surgical therapy (Monje et al, 2020). In the present study, high scores were reported for OHIP‐14, and almost all patients were satisfied with the results of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43] Thus far, most of the human research on the reconstructive treatment of peri-implantitis has involved the use of a non-submerged approach, [18][19][20][21]44 and the few studies that have used a submerged approach, have assessed slightly different outcomes or at alternative time points . 14,45,46 At this moment, no other human study has strictly assessed the outcomes of a submerged healing for peri-implantitis through direct clinical examinations of bone fill, a virtue of the necessity to remove the non-resorbable membrane and fixation screws, that we defined as our primary outcome. Therefore, a direct comparison of our results, in particular our primary endpoint to the literature may not be feasible.…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Monje et al treated 27 implants in 15 patients with peri-implantitis using a submerged healing approach . 45 Relative to the augmentation, the authors used a mixture of an autogenous and xenogenic bovine bone with the application of an absorbable collagen membrane, and assessed the outcomes with periapical radiographs at 1 year, reporting a significant gain of 2.2 mm (ranging 0 to 8.6 mm) in marginal bone levels, and 3.7 mm reduction in PD (0.7 to 5.9). 45 The many design-driven differences, and baseline characteristics of the referenced report relative to ours (the chosen biomaterials, outcome assessment, initial defect characteristics, refabrication of all crowns, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One still open question is whether after surgical reconstructive interventions, a submerged healing should be preferable. This topic has been recently investigated in a 12 months prospective case TA B L E 4 Differences pre-and 5 years treatment between-groups and intra-groups (means ± SD) PUS elimination (%) series on 15 patients rehabilitated with 27 dental implants by Monje and workers (Monje et al, 2020). The advantage of this approach would be to achieve primary wound closure and to promote an aseptic healing.…”
Section: Ta B L E 1 Patient (Implant) Sample During the Study Periodmentioning
confidence: 99%